Menilik Dominasi Bahasa Mitos Dalam Sosiokultural Sasak - Zainul muttaqin; Mu’awanah Mu’awanah (Tarbawi, 2020)
The purpose of this study is to describe the process of hegemony in the language of Tithe Ringkok Ratu myth in North Masbagik Village. The problem formulation of this research is "how is the process of hegemony in the language of the myth of Timba Lingkok Ratu in North Masbagik Village? To answer the research question above, the researcher conducted the research with qualitative descriptive method and approach with the type of ethnographic research located in North Masbagik Village Masbagik Subdistrict. Furthermore, data collection techniques from this research are observation, interview and documentation. While data analysis is data reduction, data presentation, and withdrawal conclusion. The results of this study indicate that the process of hegemony in the language of the myth of Timba Lingkok Ratu in North Masbagik Village begin beliefs that are superstition, then this belief is spread from the mouth of tempest that is by the dominant party (people who hegemonies) to the dihegemoni. Furthermore, languages that are persuasive or affect the dominant party with a style of delivery that is so reliable and with strong evidence. Therefore, it can be concluded that the process of hegemony into the language of Titus Ringkok Ratu in North Masbagik Village is a process of convincing someone who is done by the dominant party to the community against Titus Timba Lingkok Ratu in North Masbagik Village with strong evidences.